Space Back to Humanism: Research on the Development Trend and Coupling Characteristics of "Industry-City-People" in London. Issue 4 (December 2020) - Yaolin, Ran; Bingjie, Wang; Wei, Xiong; Lei, Luo
Abstract: Human-oriented development is an important issue in the world, and it also has become an important driving force for urban development and industrial upgrading in the world's major cities. So, the paper takes 33 administrative districts of London as the research object, through judging the current development trend and coupling analysis characteristics of industry, city and people in London, hoping to provide some references for the future upgrade and development of large cities. This paper constructs a human-oriented index system about the development of London's industry, city and people, and comprehensively evaluating the degree of industrial development, urbanization and people development of each administrative district of London by SPSS principal component analysis, while using the physical coupling coordination degree model to analyse the characteristics of the coupling development of London's industry, city and people. It is found that London's industrial development has the characteristics of central agglomeration and development in the direction of west, northwest and southeast. While city development also has the characteristics of central agglomeration, and it is developing towards the southwest and southeast. However, the characteristics of central agglomeration of human development are not obvious. It is developing along the south bank of the Thames and southwest of London. In addition, the coupling results of industry, city, and people systems have prominent functional hierarchy characteristics, which are obviously related to the layout of urban industrial function value areas. Finally, the paper summarizes the revelations for the development of major cities.